Field Observations on Stone Curlews in and around Kurukshetra, Haryana, India - Gupta, R.C.; Kaushik, T.K. (Our Nature, 2013)
Stone Curlew, albeit claimed to be a wader bird of wetlands, is more biased towards dry or semi-dry shores of wetlands and open grasslands in Kurukshetra environs. Although, reported to be a nocturnal bird, it was often observed in day time here. The diurnal visibility of nocturnal Stone Curlews in Kurukshetra certainly points towards its distracted, disturbed, fragmented, scarce habitat so as to compel it to take shelter beside walls in a most unsafe state. The present studies hint towards the fact that, they are summer migratory often seen between April to September but certainly not in November, December and January. They shuttle between different spot in a given area indicating its habitat range up to 1 to 3 km or so. They are facing difficult circumstances due to loss of habitat; so much so, their feeding spots are not traceable at all. This study proves that the scattered and isolated groups of a nocturnal bird like Stone Curlew are compelled to retire in full view of one and all during daytime and hence are immensely vulnerable. Their survival is threatened. Given the continuance of present adverse conditions, they will no more be seen in the next 10-15 years in Haryana, specially in Kurukshetra. DOI: http://dx.doi.org/10.3126/on.v10i1.7753